Cancer detection during the COVID‐19 pandemic—Experiences in primary care and recommendations for the future. (14th December 2022) - Siepman Van den Berg, Marinde F. R.; Grant, Matthew; van Erp, Nicole; van Gils, Carla H.; Muris, Jean; Brandenbarg, Daan; van Asselt, Kristel M.; de Wit, Niek J.; Helsper, Charles W.; ,
Abstract: Background: To describe general practitioners (GPs) experiences with the impact COVID‐19 on the duration of cancer detection. Methods: Cross‐sectional survey study among Dutch GPs. Results: Fifty‐eight GPs participated. During the first wave, COVID‐19‐related delays were experienced by 88%, 52%, and 67% of GPs in the contact‐seeking, primary care, and referral phases, respectively. GPs reported delays due to telehealth consultations, longer waiting times and patient's concerns of COVID infections and overburdening GPs. Conclusions: The majority of GPs experienced delays in cancer diagnostic processes during the beginning of the COVID pandemic, which was most prominent in the timeliness in which patients sought GP care. Abstract : A cross‐sectional study of Dutch general practitioners (GPs) was conducted to describe their experiences of the impact COVID‐19 on the duration of cancer detection in primary care. It demonstrated that the majority of GPs experienced delays in cancer diagnostic processes during the beginning of the COVID pandemic, which was most evident in the contact‐seeking phase.